B.F. Wade papers - Wade, B. F. (Benjamin Franklin), 1800-1878.
Chiefly correspondence along with printed speeches, business records, maps, and other papers relating primarily to Wade's service as U.S representative from Ohio and to national and Ohio state politics. Subjects include the elections of 1860, 1864, and 1868; secession; Civil War; U.S. Congress Joint Committee on the Conduct of the War; emancipation and suffrage for African Americans; Reconstruction; the impeachment of Andrew Johnson; Wade's law practice and business, and family affairs. Correspondents include James A. Briggs, Salmon P. Chase, Jacob D. Cox, Henry Winter Davis, Count Adam G. De Gurowski, William Dennison, John W. Forney, James A. Garfield, Joseph H. Geiger, William A. Goodlow, Abraham Lincoln, R.F. Paine, Donn Piatt, William S. Rosecrans, William Henry Seward, Green Clay Smith, Edwin McMasters Stanton, and Charles Sumner.
Microfilm edition available
Microfilm of originals in the Manuscript Division.
Lawyer, U.S. senator from Ohio, and Republican Party leader.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Briggs, James A., -- -1889 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Cox, Jacob D. -- 1828-1900 -- Correspondence; Davis, Henry Winter, -- 1817-1865 -- Correspondence; De Gurowski, Adam G., -- count, -- 1805-1866 -- Correspondence; Dennison, William, -- 1815-1882 -- Correspondence; Forney, John W. -- 1817-1881 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Geiger, Joseph H. -- Correspondence; Goodlow, William A; Johnson, Andrew, -- 1808-1875 -- Impeachment; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Paine, R. F. -- Correspondence; Piatt, Donn, -- 1819-1891 -- Correspondence; Rosecrans, William S. -- 1819-1898 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Smith, Green Clay, -- 1826-1895 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Wade family; United States. -- Congress. -- Joint Committee on the Conduct of the War; Republican Party (U.S. : 1854- ); African Americans -- Suffrage; Elections -- United States -- 1860.; Elections -- United States -- 1864.; Elections -- United States -- 1868.; Impeachments; Practice of law -- Ohio; Reconstruction (U.S. history, 1865-1877); Secession -- Southern States; Slaves -- Emancipation -- United States; Ohio -- Commerce; Ohio -- Politics and government; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1849-1877.; Lawyers; Politicians; Senators, U.S. Congress -- Ohio